Dub Writing in Marcia Douglas’ The Marvellous Equations of the Dread: A Novel in Bass Riddim - A. Harris, Treviene (Current Musicology, 2023)
Formal experimentation allows writers to critique long-standing notions of tradition and propriety. Within Caribbean literary discourse formal interventions are used to assert Caribbean life, art, and history as its own distinct expression. Particularly in relation to history and origin, or the history of our origins, Caribbean writers have experimented with literary form to articulate the region’s own peculiar understanding of its place within a time/space continuum as outside of conventional structures of knowledge. In this essay, I explore the adaptation of form across creative, artistic genres. Specifically, I look at how writing leverages sound in ways that disturb the belief that writing is a singularly privileged form in which knowledge circulates. Looking at the musical form of Jamaican Dub Music, I consider how the structural features of the sound such as fragmentation, reverb, and echo play out on the pages and in the story of Marcia Douglas’ Marvellous Equations of the Dread: A Novel in Bass Riddim. I argue that Douglas’ novel enacts what I term “dub writing” that draws on the structure of dub music and that the novel suggests how we can imagine new ways to interpret and re/present histories. These new ways—creative interventions—effectively yield versions of history in much the same way that dub music results from the versioning of an orginary text or record. Further, versions are aspirations towards destabilizing the rigid nature of linearity that sustain our conception of time and how it structures history.